ANALISIS PENGENDALIAN WAKTU DAN BIAYA DENGAN METODE EARNED VALUE PADA PROSES KINERJA PROYEK: ANALISIS PENGENDALIAN WAKTU DAN BIAYA DENGAN METODE EARNED VALUE - Kristin Yunita; Sely Novita Sari; Andrea Sumarah Asih (ReTII, 2022)
Project implementation requires a good management so that the project can achieve a planned goal. . Control in the project is the most important function in the implementation of a construction project to help ensure timeliness and quality. Project control can be done using the Earned Value method with the aim of knowing how the project costs and how the project performs every week. The research was conducted on the To’randanan Road Improvement project, To’randanan Village, Tikala sub-district, North Toraja. The project was planned for 24 weeks from May 2019 to November 2019, but experienced a delay of 7 weeks so that the implementation was carried out within 31 weeks. This Earned Value method consists of a budget and cost plan (RAB), schedule and project reports to be carried out to obtain BCWS, ACWP, BCWP, CV, SV, CPI, SPI, and EAC. Calculations are done using Microsoft Excel tools to generate tables and graphs that show how the project is performing. From the results of the application of the Earned Value method, it is known that the CPI value with poor performance is seen only in the 6th week to the 12th week. SPI values with poor performance occur at week 10 to week 24. The final cost of completing the project is IDR 4,920,249,188,11, with the difference between the cost of completion and the budget plan is a saving of IDR 268,547,811.90. Keywords: earned value, cost, time, performance